Innovation and Performance in Latin-American Small Family Firms - Maldonado-Guzmán, Gonzalo; Marín-Aguilar, José Trinidad; García-Vidales, Marisela (Asian Economic and Financial Review, 2018)
The study of innovation in family firms is gaining more and more interest among researchers and academics. Although it is a relatively recent issue in the literature, there is not enough theoretical and empirical evidence of the existing relationship with other constructs, such as the case of business performance. Therefore, using a sample of 1,400 family small businesses from 20 Latin American countries and applying a structural equations modeling of second order, which allows to know in greater depth the relationship between innovation and business performance. The fundamental objective of this empirical study is to investigate the relationship between innovation and business performance in family small business in Latin America. The results indicate that the innovation has a significant positive effect on the business performance of Latin American family small business.